A TLR4 agonist improves immune checkpoint blockade treatment by increasing the ratio of effector to regulatory cells within the tumor microenvironment - Farias, Ana (2021)
Brucella lumazine synthase (BLS) is a homodecameric protein that activates dendritic cells via toll like receptor 4, inducing the secretion of pro-inflammatory cytokines and chemokines. We have previously shown that BLS has a therapeutic effect in B16 melanoma-bearing mice only when administered at early stages of tumor growth. In this work, we study the mechanisms underlying the therapeutic effect of BLS, by analyzing the tumor microenvironment. Administration of BLS at early stages of tumor growth induces high levels of serum IFN-γ, as well as an increment of hematopoietic immune cells within the tumor. Moreover, BLS-treatment increases the ratio of effector to regulatory cells. However, all treated mice eventually succumb to the tumors. Therefore, we combined BLS administration with anti-PD-1 treatment. Combined treatment increases the outcome of both monotherapies. In conclusion, we show that the absence of the therapeutic effect at late stages of tumor growth correlates with low levels of serum IFN-γ and lower infiltration of immune cells in the tumor, both of which are essential to delay tumor growth. Furthermore, the combined treatment of BLS and PD-1 blockade shows that BLS could be exploited as an essential immunomodulator in combination therapy with an immune checkpoint blockade to treat skin cancer.